A novel post-arc current measuring equipment based on vacuum arc commutation and arc blow. (19th June 2017) - Liao, Minfu; Ge, Guowei; Duan, Xiongying; Huang, Zhihui
Abstract: The paper proposes a novel post-arc current measuring equipment (NPACME), which is based on the vacuum arc commutation and magnetic arc blow. The NPACME is composed of the vacuum circuit breaker (VCB), shunt resistor, protective gap, high-precision current sensor and externally applied transverse magnetic field (ETMF). The prototype of the NPACME is designed and controlled by optical fiber communications. The vacuum arc commutation between the vacuum arc and the shunt resistor with ETMF is investigated. The test platform is established in the synthetic short-circuit test and the vacuum arc is observed by the high speed CMOS camera. The mathematic description of the vacuum arc commutation is obtained. Based on the current commutation characteristic, the parameters of the NPACME are optimized and the post-arc current is measured. The measuring result of the post-arc current is accurate with small interference and the post-arc charge is obtained. The experimental results verify that the NPACME is correct and accurate, which can be used to measure the post-arc characteristic in breaking test.